2016
DOI: 10.5194/essd-8-543-2016
|View full text |Cite
|
Sign up to set email alerts
|

A global, high-resolution data set of ice sheet topography, cavity geometry, and ocean bathymetry

Abstract: Abstract. The ocean plays an important role in modulating the mass balance of the polar ice sheets by interacting with the ice shelves in Antarctica and with the marine-terminating outlet glaciers in Greenland. Given that the flux of warm water onto the continental shelf and into the sub-ice cavities is steered by complex bathymetry, a detailed topography data set is an essential ingredient for models that address ice-ocean interaction. We followed the spirit of the global RTopo-1 data set and compiled consist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
215
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 181 publications
(222 citation statements)
references
References 46 publications
6
215
1
Order By: Relevance
“…The meshes have 47 vertical z‐levels with thickness of 10 m in the top 100 m; vertical resolution is gradually decreasing downward. Bathymetry is taken from the RTopo‐2 data set [ Schaffer et al ., ]. The time step in simulations REF and HIGH is set to 20 and 10 min, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The meshes have 47 vertical z‐levels with thickness of 10 m in the top 100 m; vertical resolution is gradually decreasing downward. Bathymetry is taken from the RTopo‐2 data set [ Schaffer et al ., ]. The time step in simulations REF and HIGH is set to 20 and 10 min, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…We apply a minimum water column thickness of 50 m for all sub-ice cavities. An early version of RTopo-2 (Schaffer et al, 2016) has been used to derive ocean bathymetry and the ice-shelf draft and grounding lines for all cavities with fixed geometry. With the present-day ice-shelf configuration for FRIS, the FESOM mesh comprises a total of ≈ 2.6 × 10 6 nodes, 1.1 × 10 5 of which are surface nodes (where the term surface equally refers to open ocean and ice-shelf base).…”
Section: The Ocean Component: Fesommentioning
confidence: 99%
“…Both represent the presentday ice sheet, but in different spatial resolutions. The difference to the observed, high-resolution topography (Schaffer et al, 2016) is also shown in Fig. 2 …”
mentioning
confidence: 76%